Nexus água-energia-alimento no Brasil: Uma análise quantitativa dos trade-offs e sinergias - Vieira, Heris Coutinho (2025)
This study examines the Water-Energy-Food Nexus (FEW Nexus) in Brazil, focusing on the increasing demand for natural resources and the interactions between water, energy, and food sectors. Specifically, the research aims to analyze the relationships among these sectors by identifying synergies and trade-offs between 42 national indicators. Using Spearman's correlation coefficient, the study explores these interactions to promote integrated and sustainable policies. The results reveal complex dynamics, with a predominance of synergies in the energy (76,36%) and food (59,46%) sectors, while the water sector showed a more balanced distribution of synergies (52,54%) and trade-offs (40,68%). In the water sector, a positive correlation was observed between treated water volume and the area of lakes and rivers, but challenges related to water use efficiency and consumption in irrigation and industry were also identified. In the energy sector, renewable sources such as solar and wind energy proved essential for reducing CO2 emissions and improving energy efficiency, although the reliance on fossil fuels remains a significant challenge. In the food sector, agricultural production correlated positively with efficient water and energy use, but trade-offs were observed concerning child malnutrition and obesity, indicating that increased production does not always ensure food security for all. Interactions between sectors revealed that renewable energy generation can contribute to sustainable water management, while dependence on fossil fuels negatively impacts food security. The study concludes that the FEW Nexus approach is crucial for designing public policies that enhance synergies and mitigate trade-offs, aiming to achieve water, energy, and food security in Brazil. Despite limitations related to data availability and the complexity of interactions, the analysis provides valuable insights for building more sustainable and resilient agri-food systems.